2014
DOI: 10.1371/journal.pgen.1004134
|View full text |Cite
|
Sign up to set email alerts
|

High Risk Population Isolate Reveals Low Frequency Variants Predisposing to Intracranial Aneurysms

Abstract: 3% of the population develops saccular intracranial aneurysms (sIAs), a complex trait, with a sporadic and a familial form. Subarachnoid hemorrhage from sIA (sIA-SAH) is a devastating form of stroke. Certain rare genetic variants are enriched in the Finns, a population isolate with a small founder population and bottleneck events. As the sIA-SAH incidence in Finland is >2× increased, such variants may associate with sIA in the Finnish population. We tested 9.4 million variants for association in 760 Finnish sI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 59 publications
2
57
1
Order By: Relevance
“…A d v a n c e d s t a t i s t i c a l m e t h o d s a n d c l i n i c a l bioinformaticians Non-parametric statistics are preferable (e.g., median vs. mean; Mann-Whitney U-test vs. Student's T-test) because most clinical cohorts do not present normal variations anyway. It seems that the young generation has adopted, e.g., Kaplan-Meier analysis and Cox models for the handling of incomplete follow-up data and time-dependent end variables (see 7). We would suggest a few more methods to impress the reviewers and support potential readers, such as meta-analysis of previous relevant cohorts [8]; multiple imputation for missing data [1,10] at least to show that the authors were alert; competing risks analysis [4].…”
Section: Methods To Gather Local and National Follow-up Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A d v a n c e d s t a t i s t i c a l m e t h o d s a n d c l i n i c a l bioinformaticians Non-parametric statistics are preferable (e.g., median vs. mean; Mann-Whitney U-test vs. Student's T-test) because most clinical cohorts do not present normal variations anyway. It seems that the young generation has adopted, e.g., Kaplan-Meier analysis and Cox models for the handling of incomplete follow-up data and time-dependent end variables (see 7). We would suggest a few more methods to impress the reviewers and support potential readers, such as meta-analysis of previous relevant cohorts [8]; multiple imputation for missing data [1,10] at least to show that the authors were alert; competing risks analysis [4].…”
Section: Methods To Gather Local and National Follow-up Datamentioning
confidence: 99%
“…The biggest blunder in presenting a neurooncology cohort is not to have the past histological samples re-classified by neuropathologist(s)-the WHO classification is evolving continuously, and past diagnostics and subtypings are heterogeneous, even erroneous. It does not matter if there are ten authors, once the cohort and data are solid and up to date, and presented accordingly-genomic articles may contain tens or hundreds of authors [7,13].…”
Section: Multidisciplinary List Of Authorsmentioning
confidence: 99%
“…[35] A recent study revealed four novel low-frequency risk loci utilizing an alternative genetic approach. [36] The study focused on the Finnish population, enriched the percentage of familial IA patients in the discovery sample, and increased genome-wide coverage through imputing genotyped variants against the 1000 genomes project reference panel (v3, March 2012 release). [36] The first novel variant rs74972714 at 2q23.3 is located 40 Kb downstream of LYPD6.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…[36] The study focused on the Finnish population, enriched the percentage of familial IA patients in the discovery sample, and increased genome-wide coverage through imputing genotyped variants against the 1000 genomes project reference panel (v3, March 2012 release). [36] The first novel variant rs74972714 at 2q23.3 is located 40 Kb downstream of LYPD6. [36] LYPD6 can inhibit transcriptional activity of the AP-1 transcription factor complex, a key activated mediator of inflammation in endothelial cells subject to atherogenic blood flow conditions.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation